2021
DOI: 10.1051/0004-6361/202141265
|View full text |Cite
|
Sign up to set email alerts
|

The “Maggie” filament: Physical properties of a giant atomic cloud

Abstract: Context. The atomic phase of the interstellar medium plays a key role in the formation process of molecular clouds. Due to the line-of-sight confusion in the Galactic plane that is associated with its ubiquity, atomic hydrogen emission has been challenging to study. Aims. We investigate the physical properties of the “Maggie” filament, a large-scale filament identified in H I emission at line-of-sight velocities, vLSR ~−54 km s−1. Methods. Employing the high-angular resolution data from The H I/OH Recombinatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…However, the characterization of the emission in terms of filaments highlights a large number of elongated structures that are reminiscent of the plumes in the HI emission toward the outskirts of nearby spiral galaxies (Walter et al 2008). Recent studies have identified prominent elongated structures in the HI emission, for example, the 1.1-kpc-long Cattail filament with roughly 6.5 × 10 4 M (Li et al 2021) and the 1.2-kpc-long Magdalena filament with approximately 7.2 × 10 5 M (Syed et al 2022). Our results indicate that these elongated structures are the norm toward the outer Galaxy.…”
Section: Properties Of Atomic Filamentsmentioning
confidence: 96%
“…However, the characterization of the emission in terms of filaments highlights a large number of elongated structures that are reminiscent of the plumes in the HI emission toward the outskirts of nearby spiral galaxies (Walter et al 2008). Recent studies have identified prominent elongated structures in the HI emission, for example, the 1.1-kpc-long Cattail filament with roughly 6.5 × 10 4 M (Li et al 2021) and the 1.2-kpc-long Magdalena filament with approximately 7.2 × 10 5 M (Syed et al 2022). Our results indicate that these elongated structures are the norm toward the outer Galaxy.…”
Section: Properties Of Atomic Filamentsmentioning
confidence: 96%
“…Modeling the emission spectrum requires approximating the total brightness temperature emitted by the gas that would be observed in the absence of the background radio source. This is usually achieved by linear interpolation of the emission spectra in the area surrounding the source (e.g., Heiles & Troland 2003a;Murray et al 2015Murray et al , 2018Syed et al 2021). Specifically, we calculated the average spectrum taken in an annulus centered on the source with an inner radius r 1.2 in = ¢ and an outer radius r 3 out = ¢ (i.e., 4 and 10 pixels of size 18″, respectively).…”
Section: Spin Temperaturementioning
confidence: 99%
“…Syed et al 2021). Rearranging Equation (9) to use the entries in the table leads to σ nt ≈ 1 km s −1 , as entered in Table3.…”
mentioning
confidence: 99%
“…High spatial resolution observations have revealed that the H gas in the Milky Way is organised into highly filamentary structures (e.g., McClure-Griffiths et al 2006;Clark et al 2014;Martin et al 2015;Kalberla et al 2016;Blagrave et al 2017;Soler et al 2020;Skalidis et al 2022;Campbell et al 2022;Soler et al 2022;Syed et al 2022). Upon comparisons with starlight and dust polarisation data, it has been found that the elongation of these slender (with presumed widths of 0.1 pc) H filaments is often aligned with their ambient magnetic field orientations (McClure-Griffiths et al 2006;Clark et al 2014Clark et al , 2015Martin et al 2015;Kalberla et al 2016;Clark & Hensley 2019, see Skalidis et al 2022 for a counter-example).…”
Section: Introductionmentioning
confidence: 99%